Changing patterns of first e-cigarette flavor used and current flavors used by 20,836 adult frequent e-cigarette users in the USA - Christopher Russell; Neil McKeganey; Tiffany Dickson; Mitchell Nides (Harm Reduction Journal, 2018)
Abstract Background Understanding the role that flavors play in the population’s use of e-cigarettes and the impact that flavored e-cigarette products have on the population’s use of more harmful tobacco products, like conventional cigarettes, has been identified by the US Food and Drug Administration (FDA) as a public health research priority. The purpose of the study was to assess the first e-cigarette flavor and current e-cigarette flavors used by a large non-probabilistic sample of adult frequent users of e-cigarettes in the USA and assess how flavor preferences vary by cigarette smoking status and time since first e-cigarette purchase. Methods An online survey assessed the first e-cigarette flavor and current e-cigarette flavors used by a non-probabilistic sample of 20,836 adult frequent e-cigarette users in the USA. Differences in e-cigarette flavor preferences between current smokers, former smokers, and never-smokers and trends in the first flavor used across time of e-cigarette use initiation were assessed. Results The majority (n = 15,807; 76.4%) of sampled frequent e-cigarette users had completely substituted e-cigarettes for conventional cigarettes—“switchers”—and were currently using rechargeable, refillable vaping devices. Among them, the proportion of first e-cigarette purchases that were fruit-flavored increased from 17.8% of first purchases made before 2011 to 33.5% of first purchases made between June 2015 and June 2016. Tobacco-flavored first purchases almost halved during this time (46.0% pre-2011 to 24.0% between 2015 and 2016). Fruit/fruit beverage (73.9 to 82.9% of sampled users), dessert/pastry (63.5 to 68.5% of sampled users), and candy, chocolate, or sweets (48.7 to 53.4% of sampled users) were the most popular currently used e-cigarette flavors. Tobacco and menthol flavors, the two most popular flavors for initiating e-cigarette use prior to 2013, now rank as the 5th and 6th most popular currently used e-cigarette flavors, respectively. Conclusions Adult frequent e-cigarette users in the USA who have completely switched from smoking cigarettes to using e-cigarettes are increasingly likely to have initiated e-cigarette use with non-tobacco flavors and to have transitioned from tobacco to non-tobacco flavors over time. Restricting access to non-tobacco e-cigarette flavors may discourage smokers from attempting to switch to e-cigarettes.